O trabalho de enfermagem no processo de construção de um modelo assistencial em saúde coletiva - Corbishley, Angela Cristina Marques (1998)
Study the work of nursing in public health centers and its link with the global work process in Collective Health, brought together by the proposal for the organization of health services proposed by SUS (Unified Health System). The objectives of the study are: 1) Characterize the work of nursing, as well as its relation to the work of other health professionals in different Public Health Centers in SUS/JF, Juiz de Fora, MG, Brazil; 2) Discuss the practice of nursing considering proposed changes to the health welfare work model in Juiz de Fora; 3) Analyze the work in nursing in the context of the construction of SUS, within the work process of Collective Health. A qualitative research was conducted, which utilized dialectical materialism as the method of investigation. The fundamental history and concepts of Collective Health, the work process in health care and the health welfare work model proposed by SUS were used as references. ln this study, the thesis was confirmed that the work of nursing in Public Health Centers, characterized by the different types ex.isting in Juiz de Fora, accompanies the work in Collective Heath in Brazil.